On the interpretation of signs of unauthorized construction: the philosophical and legal aspect - Tkachenko, V. S.; Ткаченко, В. С. (Visegrad journal on human rights. – 2018. – № 4 (Vol. 2). – P. 103-106, 2018)
У статті здійснено доктринальний аналіз ознак об’єкта самочинного будівництва. Досліджено етимологічні особливості через призму базових філософських категорій. Проаналізовано лінгвістичний і правовий аспекти відокремлених законодавцем ознак самочинно зведеного об’єкта нерухомості.

The article deals with the doctrinal analysis of the signs of self-constructed construction. The etymological features are studied through the prism of basic philosophical categories. The linguistic and legal aspects of the property of a self-contained consolidated property are set out by the legislator.

В статье проведен доктринальный анализ признаков объекта самовольного строительства. Исследованы этимологические особенности через призму базовых философских категорий. Проанализирован лингвистический и правовой аспекты обособленных законодателем признаков самочинно возведенного объекта недвижимости.
Щодо тлумачення ознак самочинного будівництва: філософсько-правовий аспект
Keywords: нерухомість; самочинне будівництво; філософсько-правовий аспект; real estate; unauthorized construction; philosophical and legal aspect; недвижимость; самовольное строительство; философско-правовой аспект